Pelatihan Public Speaking Bagi Tenaga Kerja Indonesia di Malaysia - Puspasari, Durinda; Puspasari, Durinta; Wulandari, Ruri Nurul Aeni; Panduwinata, Lifa Farida (Universitas Negeri Surabaya, 2025)
Indonesian workers are the second largest contributor of foreign exchange after oil and gas. Therefore, it is important to empower the group of Indonesian workers working abroad. This is needed to address the issue of Indonesian workers working abroad. Empowerment of workers can be done through training programs that can provide education to workers according to their respective interests and needs, one of which is public speaking. Through public speaking, it will train self-confidence to appear in the public realm or to the wider community. Public speaking training was held in Selangor, Malaysia, which was attended by 26 participants from AOMI (Aliansi Organisasi Masyarakat Indonesia) and lecturers who are members of the PKM group from the Office Administration Education Study Program, Surabaya State University. This community service activity was carried out in the form of training with lecture methods and public speaking practices for workers who are members of AOMI Malaysia. The implementation of community service activities by the PKM Team received a very good response, which can be seen from the questionnaire response data of 46.2% stating good and 34.6% stating very good, as well as testimonials from Indonesian workers in Malaysia regarding public speaking training which were responded positively. So that the training participants were very enthusiastic to follow this PKM activity until it was finished and the training participants wanted to be able to carry out similar workshop activities in the future, in order to support the development of their communication skills in a sustainable manner.